Pemahaman Kaidah Penulisan Soal dan Pengalaman Menulis: Dampaknya terhadap Kemampuan Menulis Soal Bahasa Indonesia - Ulviani, Maria (AIJER: Algazali International Journal Of Educational Research, 2024)
This research aims to obtain, analyze and describe data regarding (1) The influence of teachers' understanding of questions writing rules on the ability to write Indonesian language questions of Unismuh Elementary School teachers in Makassar, (2) The influence of teacher question menu experience on the ability to write Indonesian language questions of Unismuh Elementary School teachers Makassar, (3) The influence of understanding the rules for writing questions and the teacher's experience of writing questions together on the Indonesian language question writing ability of Unismuh Elementary School teachers in Makassar. This type of research is survey research with correlative techniques. The research population is all elementary school teachers at Unismuh Makassar for the 2023/2024 school year. The population was 18 people with the sampling technique being total sampling. The results of this research show that (1) There is a significant influence between the variable understanding of writing rules on the ability to write questions in Indonesian at Unismuh Makassar Elementary School teachers, with a large influence of 59.70%, (2) there is a significant influence between the variable experience of writing questions on Unismuh Makassar Elementary School teachers' ability to write Indonesian language questions with a large influence of 55.29%. (3) There is a significant influence simultaneously on understanding the rules for writing questions and experience writing questions on the Indonesian language question writing ability of Unismuh Makassar Elementary School teachers with a large influence of 59.66%.